Adipose‐derived factor CTRP9 attenuates vascular smooth muscle cell proliferation and neointimal formation. Issue 1 (12th September 2012) - Uemura, Yusuke; Shibata, Rei; Ohashi, Koji; Enomoto, Takashi; Kambara, Takahiro; Yamamoto, Takashi; Ogura, Yasuhiro; Yuasa, Daisuke; Joki, Yusuke; Matsuo, Kazuhiro; Miyabe, Megumi; Kataoka, Yoshiyuki; et al.
Abstract : Obesity is closely associated with the progression of vascular disorders, including atherosclerosis and postangioplasty restenosis. C1q/TNF‐related protein (CTRP) 9 is an adipocytokine that is down‐regulated in obese mice. Here we investigated whether CTRP9 modulates neointimal hyperplasia and vascular smooth muscle cell (VSMC) proliferation in vivo and in vitro. Left femoral arteries of wild‐type (WT) mice were injured by a steel wire. An adenoviral vector expressing CTRP9 (Ad‐CTRP9) or β‐galactosidase as a control was intravenously injected into WT mice 3 d before vascular injury. Delivery of Ad‐CTRP9 significantly attenuated the neointimal thickening and the number of bromode‐oxyuridine‐positive proliferating cells in the injured arteries compared with that of control. Treatment of VSMCs with CTRP9 protein attenuated the proliferative and chemotactic activities induced by growth factors including platelet‐derived growth factor (PDGF)‐BB, and suppressed PDGF‐BB‐stimulated phosphorylation of ERK. CTRP9 treatment dose‐dependently increased cAMP levels in VSMCs. Blockade of cAMP‐PKA pathway reversed the inhibitory effect of CTRP9 on DNA synthesis and ERK phosphorylation in response to PDGF‐BB. The present data indicate that CTRP9 functions to attenuate neointimal formation following vascular injury through its ability to inhibit VSMC growth via cAMP‐dependent mechanism, suggesting that the therapeutic approaches to enhance CTRP9 production could be valuable for prevention of vascular restenosis after angioplasty.—Uemura, Y., Shibata, R., Ohashi, K., Enomoto, T., Kambara, T., Yamamoto, T., Ogura, Y., Yuasa, D., Joki, Y., Matsuo, K., Miyabe, M., Kataoka, Y., Murohara, T., Ouchi, N. Adipose‐derived factor CTRP9 attenuates vascular smooth muscle cell proliferation and neointimal formation. FASEB J. 27, 25–33 (2013). www.fasebj.org